What could happen after the first wave of COVID-19 diffusion in Italy: learning from the 1918 influenza pandemic - Fabiano, Nicola; Radenović, Stojan (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: A comparison of the 1918 “Spanish” influenza to the 2020 COVID–19 pandemic could shed some light on the evolution of the latter. Method: A mathematical method previously applied to the description of the behavior of the spread of COVID–19 in time is used this time to the 1918 influenza. Results: The obtained results were compared and some conclusions made about some possible forecasts for the next waves of COVID-19. Conclusions: Some further waves of the 2020 pandemic should be expected in the future.